2007
DOI: 10.2967/jnumed.106.035535
|View full text |Cite
|
Sign up to set email alerts
|

Total Thyroidectomy and Adjuvant Radioiodine Treatment Independently Decrease Locoregional Recurrence Risk in Childhood and Adolescent Differentiated Thyroid Cancer

Abstract: We sought to assess whether extensive surgical treatment, postsurgical radioiodine therapy, or both decrease the risk of locoregional recurrence (LR) after curative primary treatment in children and adolescents diagnosed with differentiated thyroid cancer (DTC) at age #18 y. Methods: To determine the incidence of and identify predictive factors for thyroid bed recurrence (TBR) or lymph node recurrence (NR), we performed a chart review and retrospective multivariate Cox regression analysis on 235 patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
143
2
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(158 citation statements)
references
References 36 publications
9
143
2
4
Order By: Relevance
“…These data correlate with previously reported recurrence rates of 19%-24% (10,15,16). However, wider ranges (11%-32%) have been reported (12,(17)(18)(19)(20)(21), as have ranges as high as 39%-46% (5,22,23).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These data correlate with previously reported recurrence rates of 19%-24% (10,15,16). However, wider ranges (11%-32%) have been reported (12,(17)(18)(19)(20)(21), as have ranges as high as 39%-46% (5,22,23).…”
Section: Discussionsupporting
confidence: 91%
“…The difference in the probabilities of recurrence between patients in group 1 and patients in group 3 was highly significant (P 5 0.001). Nevertheless, some authors have reported that age is not a significant risk factor for recurrent disease (19,28).…”
Section: Discussionmentioning
confidence: 98%
“…Several studies from Western countries have demonstrated that total thyroidectomy offers a better prognosis than hemithyroidectomy [9][10][11][12][13][14][15][16][17]. These results might be low grade evidence, because there were not including randomized studies in almost of these reports.…”
Section: Surgical Treatment (Thyroidectomy)mentioning
confidence: 99%
“…Total thyroidectomy remains the preferred operation in tumors greater than T1a (>1cm). It is generally accompanied by dissection of the central lymphatic compartment since local lymph node disease increases www.intechopen.com the risk of local and regional recurrence (Parisi, 2007, Niedziela, 2006, Handkiewicz, 2007. Patients who undergo total thyroidectomy have a higher rate of recurrence-free survival.…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…Nodal recurrences are more frequent in patients with the histologic subtype of papillary carcinoma, classical variant as compared to the follicular variant. Specifically, the 10 year nodal recurrence free survival has been reported at 83% for papillary carcinoma, classic type vs. 95% for the follicular variant type (Parisi, 2006, Luster, 2007, Handkiewicz, 2007.…”
Section: Post-surgical Evaluation and Radioiodine Treatmentmentioning
confidence: 99%